The relationship between coronavirus disease 2019 (COVID-19) vaccines, abnormal uterine bleeding, and hormonal disorders in women of reproductive age: one-center cross-sectional results - Ghonche Jahani; Nazanin Hojjati (Golestan University Of Medical Sciences, 2023)
Background: Changes in menstrual bleeding in the context of hormonal changes may explain why reports on this phenomenon were published globally during the COVID-19 vaccination period. This study was designed to investigate the relationship between the injection of COVID-19 vaccines, abnormal uterine bleeding (AUB), and hormonal disorders in women of reproductive age who were referred to Sayad Shirazi Hospital in Gorgan (Iran) in 2023. Methods: This cross-sectional study was conducted on patients referred to the Gynecology Center of Sayad Shirazi Hospital (Gorgan). The census method was used for collecting data, and the data of 114 women of reproductive age information who had received at least 1 dose of the COVID-19 vaccine were collected by a questionnaire and analysis of requested tests and their registration and analyzed in SPSS v. 16. Chi-square, independent t-test, and analysis of variance were used, and the significance level was <0.05. Results: In this study, 114 women with an average age of 41.12 years met the inclusion criteria; 27 women had previous abnormal bleeding patterns, which had a clear change in the bleeding process, and the rest had a regular cycle with AUB. Three types of vaccines were used by the women; AstraZeneca had the most side effects, followed by Sinopharm. The participants showed abnormal bleeding during the first year, although in most women, it had started in the first 6 months. COVID-19 vaccination showed a significant relationship with the change in the bleeding process (P=049). Coagulation disorders and partial thromboplastin time (PTT) of more than 35 did not show a significant relationship between disorders, specific hormones, and AUB (P=0.269). However, the presence of hormonal disorders with AUB, despite increased PTT, had a significant relationship with AUB (P=0.011). Conclusion: The results indicated a significant relationship between the injection of vaccines and the occurrence of AUB regardless of hormonal disorders and coagulation disorders, which were more likely to occur in a wider time frame (6 months or more). The results also demonstrated that these side effects were expected among people who receive the vaccine; for health care workers, on the other hand, trying to correct and prevent more side effects. Although different types of vaccines can cause different effects, their long-term effects should be considered, especially in women with the possibility of hormonal changes and abnormal bleeding, and the use of vaccines with fewer complications is recommended.